Sen's capability approach and microcredit: lessons from a Malaysian case. Issue 2 (17th February 2019) - Nambiar, Shankaran
ABSTRACT: This article examines a case study from Malaysia, the Credit Union Malaysia, to illustrate how the capability framework and institutions have practical value within the scope of microcredit, and how the constraints that the disadvantaged face can be relaxed through the use of microcredit. The capability approach provides an analytical framework to describe how a microcredit scheme can overcome the problems posed by conversion factors in order to enlarge the space of capabilities available to individuals.